(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Pesantren Hurriyatul Amiin, located in Parung, Bogor Regency, is an Islamic boarding school that educates underprivileged students from economically disadvantaged backgrounds. Currently, the pesantren accommodates approximately 30 students who study free of charge. Educational and operational support is provided by the pesantren management and donors. This community service activity aims to empower the pesantren’s economy through training and mentoring in developing a small-scale herbal liquid soap industry. The activities consist of: (1) entrepreneurship training for the pesantren management and students; (2) practical training in herbal liquid soap production; and (3) mentoring in preparing production facilities and conducting small-scale industrial production trials. The methods include presentations, discussions, entrepreneurship simulations, practical laboratory soap production, and guidance in building the production room. The results show that the management and students have improved their cognitive and psychomotor skills related to entrepreneurship and herbal soap production. The provision of machinery, equipment, and raw materials facilitated the mentoring process and enabled a 5-liter small-scale production trial. This community service activity has fostered optimism among the pesantren management to sustain continuous production and ensure the financial benefits support pesantren operational costs.